2015
DOI: 10.1007/s40615-015-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Adverse Drug Events: A Systematic Review of the Literature

Abstract: The 2014 National Action Plan for Adverse Drug Event Prevention has recognized adverse drug events (ADEs) as a national priority in order to facilitate a nationwide reduction in patient harms from these events. Throughout this effort, it will be integral to identify populations that may be at particular risk in order to improve care for these patients. We have undertaken a systematic review to evaluate the evidence regarding racial or ethnic disparities in ADEs with particular emphasis on anticoagulants, diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 53 publications
1
44
0
1
Order By: Relevance
“…A recent systematic review found no consistent relationship between race and ADRs in general but noted that certain racial groups may be at higher risk for ADRs due to certain classes of agents (18). Asians were found to be higher risk for ADRs from oral anticoagulants whereas blacks were at higher risks from antidiabetic agents and whites from opiate analgesics (18). In a study of United States Vital Statistics, deaths due to ADRs were significantly more frequent in African-Americans than Caucasians, Hispanics, or Asians (19).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found no consistent relationship between race and ADRs in general but noted that certain racial groups may be at higher risk for ADRs due to certain classes of agents (18). Asians were found to be higher risk for ADRs from oral anticoagulants whereas blacks were at higher risks from antidiabetic agents and whites from opiate analgesics (18). In a study of United States Vital Statistics, deaths due to ADRs were significantly more frequent in African-Americans than Caucasians, Hispanics, or Asians (19).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence relating to ADEs among ethnic minorities was mixed and was observed to depend on contextual features such as geographical, genetic and cultural features [35,57,59]. Metersky White et al [12] 2012 Australia Primary Focus groups (n = 2) with…”
Section: Review Q 2: What Is the Evidence For Patient Safety Events Imentioning
confidence: 99%
“…• Chinese participants had doubts about the their systematic review observed that Asians were more prone to ADEs related to anticoagulants such as bleeding and African American to ADEs relating to diabetes agents such as hypoglycaemia [35]. The term Asian represented combined Asian/Pacific Islander group but authors did not specify any specific ethnic minority group from Asia.…”
Section: Review Q 2: What Is the Evidence For Patient Safety Events Imentioning
confidence: 99%
“…Women were classified as "food secure" if they reported no more than 2 food-insecure conditions and "food insecure" if they reported 3 or more. Financial difficulties and housing disrepair were measured using the Survey of Income and Program Participation [16]. Difficulties paying bills was assessed using the questions (1) "Have you had serious financial problems or been unable to pay monthly bills, rent, or mortgage during the past 12 months?…”
Section: Psychosocial Stressorsmentioning
confidence: 99%